Moisture retaining test of biochar, coco coir peat, palm kernel oil cake and charcoal dust mixtures for grounding system purposes - Wan Ahmad, Wan Fatinhamamah Binti; Nagappan, Y. (Institute of Electrical and Electronics Engineers, 2024)
A grounding system provides a safe path for electric current to dissipate into the Earth, protecting both personnel and equipment from electrical faults especially during the event of lightning. Thus, a good grounding system is the ones that provides the lowest resistance path for fault currents to flow safely into the earth at the shortest time possible. There are multiple ways of achieving the lowest resistance path for the ground conductor. One of the methods is by installing enhancement materials in the vicinity of ground conductors. Although there are two types of enhancement material which are chemical and natural, only natural type has been tested in this work due to its environmentally friendly properties, i.e. Biochar, Coco Coir Peat, Palm Kernel Oil Cake and Charcoal Dust. There were 20 samples involved which consisted of 4 individual NEM and 16 NEM mixed samples with various ratios. The main objective of this work is to find the best performing NEM mixture for the grounding system purposes within the 20 samples, by conducting the Moisture Retaining Test twice a week starting from 25th January 2024 till 23rd May 2024 for a total of 17 weeks. It was concluded that the performance of best five NEM mixtures in descending order were found to be 100% Biochar, Biochar: Charcoal Mix A, Biochar: Charcoal Mix B, 100% Charcoal Dust and Biochar: Charcoal Mix C with their percentage of weight comparisons to their day-0 weight were found to be 66.38%, 65.46%, 64.70%, 64.63% and 64.47%, respectively.